2018
DOI: 10.1182/bloodadvances.2017006668
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of snoRNAs in normal hematopoiesis and AML

Abstract: Key Points• A subset of snoRNAs is expressed in a developmental-and lineage-specific manner during human hematopoiesis.• Neither host gene expression nor alternative splicing accounted for the observed differential expression of snoRNAs in a subset of AML.Small nucleolar RNAs (snoRNAs) are noncoding RNAs that contribute to ribosome biogenesis and RNA splicing by modifying ribosomal RNA and spliceosome RNAs, respectively. We optimized a next-generation sequencing approach and a custom analysis pipeline to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 62 publications
3
68
1
Order By: Relevance
“…NGS-based analysis of snoRNAs is more tricky as their size, ranging from 60 to 250 nucleotides [187], overlaps with a gap between conventional small RNA sequencing and RNA-seq, devoted to mRNAs and other RNA molecules longer than 200 nt. Developing their own sequencing approach, Warner et al [188] showed that snoRNAs, e.g., orphan snoRNAs contained in the imprinted DLK-DIO3 and SNURF/SNRPN loci, are expressed in a lineage- and developmentally restricted manner in human hematopoiesis. Moreover, 120 snoRNAs, including SNORA21 , SNORA36C and SCARNA15 , displayed consistent differential expression in AML, and, what is even more interesting, all of them were decreased in AML samples compared to normal CD34+ cells.…”
Section: Snornamentioning
confidence: 99%
See 1 more Smart Citation
“…NGS-based analysis of snoRNAs is more tricky as their size, ranging from 60 to 250 nucleotides [187], overlaps with a gap between conventional small RNA sequencing and RNA-seq, devoted to mRNAs and other RNA molecules longer than 200 nt. Developing their own sequencing approach, Warner et al [188] showed that snoRNAs, e.g., orphan snoRNAs contained in the imprinted DLK-DIO3 and SNURF/SNRPN loci, are expressed in a lineage- and developmentally restricted manner in human hematopoiesis. Moreover, 120 snoRNAs, including SNORA21 , SNORA36C and SCARNA15 , displayed consistent differential expression in AML, and, what is even more interesting, all of them were decreased in AML samples compared to normal CD34+ cells.…”
Section: Snornamentioning
confidence: 99%
“…No somatic mutations were detected in the snoRNA genes, either. By the way, the authors found a few novel snoRNAs and proved standard transcriptome sequencing cannot reliably distinguish unspliced primary host gene RNA from correctly processed snoRNA [188].…”
Section: Snornamentioning
confidence: 99%
“…In fact, our data suggest that the sequence flanking miRNAs and snoRNAs indeed contribute to payload processing. Other, more dynamical effects, such as a potential contribution of host gene abundance to the regulation of payload (Baskerville and Bartel 2005;Warner et al 2018), on the other hand, cannot be assessed at sequence level alone and thus have to remain a topic for future research. Similarly, indirect links between miRNAs and sdRNAs (snoRNA-derived sRNAs) on factors that regulate hostgene transcription as well as direct interactions of the payload with the hostgene, known, e.g., in the case of let-7 (Jiao and Slack 2012;Minchington et al 2020) are beyond the scope of this contribution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, snoRNAs and their host genes have attracted renewed attention and have been recognized as new players in cancers (Williams and Farzaneh, 2012; McMahon et al, 2015). Several recent studies reported the general downregulation of a number of snoRNAs in normal hematopoiesis and leukemia (Valleron et al, 2012; Ronchetti et al, 2013; Warner et al, 2018). However, AML1–ETO, AML1–ETO9a, and MLL–AF9 enhanced snoRNA expression, and similar results were obtained in t(8;21) patient samples compared with purified CD34 + progenitor cells or normal bone marrow (Zhou et al, 2017).…”
Section: Ncrna Dysregulation Is Linked To Chromosomal Translocationmentioning
confidence: 99%
“…Overexpression of the 14q32 snoRNA transcripts located at the DLK1-DIO3 locus is believed to be related to fusion transcripts harboring the RARA gene (Cohen et al, 2012). Neither host gene expression nor alternative splicing and mutations accounted for the aberrant expression of snoRNAs (Valleron et al, 2012; Warner et al, 2018). Further analyses of the underlying mechanisms are needed.…”
Section: Ncrna Dysregulation Is Linked To Chromosomal Translocationmentioning
confidence: 99%